Body Weight, Physiological Status and Volatile Fatty Acid on Kacang and Etawah Crossbreed Goat by Reduction and Refeeding of Feed Quantity - Bambang Suwignyo; Panjono Panjono; Aryanto Aryanto; Sarmin Sarmin; Irkham Widiyono (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2018)
The aimed of this study was to observe the effect of feed restriction and refeeding on body weight, physiological status and blood VFA on Kacang and Etawah Crossbreed Goat. Eight male goats consisting of 4 Kacang Goats and 4 Etawah Crossbred goats were used as experiment objects in this study. Both types of goats were subjected to the same treatment (three phases). First was adaptation, feed was given gradualy until reach the intended amount. Secondly, the feed was reduced by giving as much as 1.7% dry matter of body weight for each; thirdly, both goats were fed on ad libitum (refeeding phase). The variables observed were body weight changes, physiological status and blood VFA. The data obtained were analyzed by Various Random Test using Completely Randomized Design (RAL) on 2x2 factorial patterns. Duncan Multiple Range Test was used to test treatments that significantly different. The results showed that the pattern of changes in body weight on both goats breeds were relatively similar. Physiological status (pulse, rectal and respiratory temperature) on both breed of goats were not significantly different. However, decrease in the amount of feed impacted in the decrease in body temperature, pulsus and respiration, although it was still within normal range. The same also happened on blood VFA levels. Based on the results of the study, it can be concluded that breed differences breed of goat did not affect the physiological condition of goat. Differences in the amount of feed affect the physiological conditions and the performance of goat production.